Bombus lucorum ... - Pauly, Alain (Zenodo, 2018)
Bombus lucorum (Linné, 1761) 17.VII.1978, 1D, Campanula rotundifolia; 21.VII.2013, 1D, lande, fauchoir talus. ... : Published as part of Pauly, Alain, 2018, Les abeilles sauvages de la lande de Streupas (Hymenoptera: Apoidea), pp. 1-36 in Belgian Journal of Entomology 60 on page 20, DOI: 10.5281/zenodo.13619251 ...